LRFD Analysis for Semi-Rigid Frame Design - King, Won Sun; Chen, Wai-Fah (Engineering Journal, 1993)
A practical LRFD-based analysis method for the design of semi-rigid frames is proposed. The proposed method uses first-order elastic analysis with a notional lateral load for the second-order effects. In the proposed method, a simplified three-parameter model describing the tangent rotational stiffness of semi-rigid connections is used.